The effect of intellectual capital on entrepreneurial opportunity recognition - Kambeiz Talebi; Ali Davari; Amer Dehghan najmabadi (مطالعات مدیریت بهبود و تحول, 2013)
Organizations are entering to the knowledge based economy which in science and intangible assets are known as the most important competitive advantage for them. The present research aims to investigate the effect of intellectual capital on entrepreneurial opportunity recognition at knowledge based firms in Yazd’s science and technology park of Eghbal. Our statistical population contains 75 managers of knowledge based firms in Yazd’s science and technology park of Eghbal. Due to the limited numbers of managers, the census method was applied for sampling. The two standard questionnaires (Moon & Kym, 2006 and Puhakka, 2010) were used for gathering data. Structural equation modeling with smart PLS 2 software was applied for analyzing data in two sections of measurement model and structural model. In measurement model section, technical features of the questionnaire in terms of reliability, convergent validity, and discriminant validity were investigated. Moreover, in structural model section, path coefficients were used for testing hypotheses. The results indicate the positive and significant effect of intellectual capital and its dimensions on entrepreneurial opportunity recognition at knowledge based firms in our sample. Besides, we conclude that intellectual capital is a potential source for knowledge based firms’ competitive advantages that consequently leads to the growth and development of these firms and getting a better situation of entrepreneurship in them.